Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1365-2486.2010.02299.x
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the effects of global change scenarios on bioaccumulation patterns in great lakes species

Abstract: Climate change will have substantial impacts on biodiversity, particularly for aquatic species. Warming temperatures and changing weather patterns will also remobilize and modify chemical partitioning. Holding millions of cubic yards of sediments contaminated with persistent legacy chemicals such as polychlorinated biphenyls (PCBs) and dioxins, the Laurentian Great Lakes are a laboratory for observing interactions between biological and chemical responses to climate change. They provide a wide range of habitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…At higher trophic levels, initial increases in richness will promote changes in predation and competition pressures that can strongly affect final community composition. Sharma et al (2007) argued that increased predation by invading smallmouth bass would pose a serious threat to native cyprinid species (as per Jackson 2002), while Ng and Gray (2011) argued that climate driven shifts in predator-prey relationships could cause increased bioaccumulation of persistent chemicals in freshwater food chains. Buisson and Grenouillet's (2009) study of climate change impacts on French rivers suggested that species diversity would increase more than trait diversity in many locations, leading to increases in the overall intensity of competition for resources (e.g.…”
Section: Sensitivity To Climate Change Is Shaped By Winter Strategiesmentioning
confidence: 99%
“…At higher trophic levels, initial increases in richness will promote changes in predation and competition pressures that can strongly affect final community composition. Sharma et al (2007) argued that increased predation by invading smallmouth bass would pose a serious threat to native cyprinid species (as per Jackson 2002), while Ng and Gray (2011) argued that climate driven shifts in predator-prey relationships could cause increased bioaccumulation of persistent chemicals in freshwater food chains. Buisson and Grenouillet's (2009) study of climate change impacts on French rivers suggested that species diversity would increase more than trait diversity in many locations, leading to increases in the overall intensity of competition for resources (e.g.…”
Section: Sensitivity To Climate Change Is Shaped By Winter Strategiesmentioning
confidence: 99%
“…Ng and Gray 17 focused their investigation of bioaccumulation and climate change on the impact of projected temperature increases in the Great Lakes on the metabolic rates of fish with different thermal sensitivities. Their study considered only PCB-77 and did not consider changes in the productivity or organic carbon content of the water column.…”
Section: Applying Quantitative Tools To Estimate Gcc Impacts On Chemimentioning
confidence: 99%
“…Consumption and growth rates, which are positively correlated in bioenergetics models but negatively correlated in bioaccumulation models, were predicted to have a balancing effect on the influence of temperature on chemical concentrations in biota. Changes in PCB-77 concentrations in fish due to projected temperature shifts in Lake Erie and Lake Superior were relatively small, particularly when compared with potential changes in food availability and food type 17. Metabolic effects (temperature effects on the rate of chemical uptake and loss) were confounded by trophic interactions among species with different thermal sensitivities, indicating possible effects of invasions of warm-water species into warming higher-latitude territories 17.…”
Section: Applying Quantitative Tools To Estimate Gcc Impacts On Chemimentioning
confidence: 99%
See 2 more Smart Citations